Inexpensive Heating Reduces Winter Mortality - Janjala Chirakijja; Seema Jayachandran; Pinchuan Ong (Institute of Labor Economics (IZA), 2019)
This paper examines how the price of home heating affects mortality in the US. Exposure to cold is one reason that mortality peaks in winter, and a higher heating price increases exposure to cold by reducing heating use. It also raises energy bills, which could affect health by decreasing other health-promoting spending. Our empirical approach combines spatial variation in the energy source used for home heating and temporal variation in the national prices of natural gas versus electricity. We find that a lower heating price reduces winter mortality, driven mostly by cardiovascular and respiratory causes.
Keywords: I1; J14; Q41; 330; weather-related mortality; winter mortality; energy prices; energy poverty; fuel poverty